Calidad del agua del río Chipe y su aptitud para actividades recreativas en el cantón Valencia, provincia de los ríos. Año 2018. - Guzmán Acurio, Jenny Alexandra (2018)
This work was carried out in the river Chipe of the canton Valencia, province of the rivers, whose general objective was to evaluate the quality of water and its aptitude for recreational activities and its specific ones were: to carry out a diagnosis on the current state of the water source in A segment of the river Chipe, analyze water quality parameters in the area under study to be compared with the current environmental regulations and determine the water pollution Index (ICOMI). It was based on the hypothetical-deductive method and the non-experimental design was applied, which consisted in taking periodic samples of water for in situ measurements and sampling for laboratory analyses. Graves were identified for the burning of waste, turbid water, plastic waste stopped in branches of crossed trees. Water quality parameters in the spa area resulted in: hydrogen potential in the rainy season a lower value of 6.28 of the maximum permissible range; Oils and fats the value is higher than the permissible limit 0.44 in the two times when the regulation allows 0.3 mg/L, the most notable aspect is the high number of total coliforms-NMP reaching levels of 38730 NMP/100 ml in the rainy season and 24196 NMP/100 ML In dry season at sampling points, whereas TULSMA (2012) determines 1000 NMP/100 ml. Upstream there are no high values to consider, but 46110 NMP/100ml was determined in coliforms for the rainy season and 24197 NMP/100ml for the dry season. The Water Pollution Index (ICOMI) determined that no mineralization contamination is present.